INTEGRATION OF LOCAL WISDOM IN NIAS MYTHS ABOUT NATURAL PHENOMENA AS A BASIS FOR DEVELOPING SCIENCE LEARNING AND STRENGTHENING SCIENTIFIC ARGUMENTATION - Darmawan Harefa (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to explore the potential of Nias myths and local wisdom in the development of science learning (Natural Sciences) and the strengthening of students’ scientific argumentation skills. The method employed is a library research approach with a systematic framework, including the identification, evaluation, and synthesis of literature related to local wisdom, ethnoscience, cultural narratives, the integration of culture into science learning, and the development of scientific argumentation. The findings indicate that Nias myths contain knowledge of natural phenomena that can serve as a contextual, relevant, and meaningful learning context for students. The narrative structure of the myths facilitates the extraction of scientific concepts, the development of cause-and-effect reasoning, and the understanding of human-environment interactions, thereby enhancing scientific literacy and critical thinking skills. The integration of local wisdom into science learning also supports the development of scientific argumentation, as students are trained to construct claims, link evidence, reason logically, and compare traditional perspectives with modern scientific knowledge. This study emphasizes that Nias myths are not merely cultural heritage but also an effective pedagogical resource for culturally based science education. The implications of this research can serve as a foundation for developing contextual science learning modules and teaching strategies that combine local cultural identity with scientific competencies.